PENINGKATAN MUTU PEMBELAJARAN MELALUI MANAJEMEN INOVASI DAN KREATIVITAS GURU DI SEKOLAH - Fadliyah Nurbayyinah; Muhammad Nurjamaludin; Siti Zulfa Nurul Iqomah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Education plays a very important role in the social, economic, and cultural development of a nation. Teachers, as the main element in the education process, play a major role in improving the quality of learning. This study aims to explore the importance of innovation management and teacher creativity in improving collaborative learning in schools. The method used is qualitative research with a literature study approach, which collects data from related books, articles, and journals. The results of the study indicate that effective innovation management can improve the quality of learning through the application of technology, curriculum development, and more optimal resource management. Creative teachers are able to create a pleasant learning atmosphere, which has a direct impact on student motivation and learning outcomes. The study also emphasizes that to support this innovation, the active role of the principal, parents, and the community is needed in creating a climate that supports teacher creativity. In addition, this study recommends that educational policies that support the implementation of innovation continue to be strengthened and pay attention to supporting factors such as teacher training and the use of technology in learning. Further research can further examine the application of specific technology in learning and the role of the principal in supporting educational innovation.